Hidden in Folklore: The Past and Present of the Revival Movement in Post-Socialist Countries - Stavělová, Daniela (Traditiones, 2023)
The study points to the ambivalence and ambiguity of the folklore movement, which in the environment of the former socialist Czechoslovakia was sometimes associated with the expression “hiding in folklore”, describing in particular the act of creating an alternative space to the everyday reality that did not allow a person to fully self-realize or express their own identity. We ask to what extent this metaphor represents the nature of todayʼs folkloric activities in the post-socialist society.